Pelaksanaan Fungsi Pengawasan BUMDes Desa Ponggok Kecamatan Polanharjo Kabupaten Klaten - Putri Febri Astuti; Warsito . (Journal of Politic and Government Studies, 2017)
ABSTRACT Village owned enterprises or BUMDes is an enterprise in which all or most of the financial capital is owned by the village where the financial capital is directly comes from the wealth of the village itself which is separated to manage assets, services, and other exertion to increase the welfare of society. ’’BUMDes Tirta Mandiri Desa Ponggok’’ is one of an advanced  enterprise which gives a real contribution for the village economic development, the village infrastructure development, social aid and financial capital. There are two implementation control of Bumdes Tirta Mandiri, those are internal control and external control. Internal control is organized by ’’Badan Pengawas’’ whereas external control is organized by ’’Bapermas’’.The research method that is used is qualitative research. The data were collected by observation, interview, and literary review as the data collecting technique. The informants of this research are the Director of BUMDes Tirta Mandiri Desa Ponggok, ’’Badan Pengawas Tirta Mandiri Desa Ponggok’’, the Village Head of Ponggok, the Head of BPD Desa Ponggok, the Head of Bapermas Klaten.The result of this research showed that the election process of the supervisors affect the supervisors’ work since it influential a supervisor’s quality. The implementation control by ’’Badan Pengawas’’ is organized objectively because ’’Badan Pengawas” use its standard that is tool administration, besides that, the implementation control is organized periodically which is arranged in the annual work program. However, there is a problem in the implementation control, the problem is the coordination between ’’Badan Pengawas’’ and BUMDes management are stymied by the adjusting of the meeting time, therefore, it hasn’t run optimally, since ’’Bapermas’’ only plays a role in the beginning of the election and as a facilitator in the provincial government program. The recommendation for BUMDes Management are organizing the training and the orientation towards ’’Badan Pengawas” and need to create a framework coordination for ”Bapermas” as the Vice-Regent in order to increase the role of BUMDes Tirta Mandiri’s monitoring and evaluation, although BUMDes Tirta Mandiri is categorized as a independent BUMDes and need to arrange the technical rules of monitoring and evaluation. Keywords: BUMDes Tirta Mandiri, control